2012
DOI: 10.1093/cid/cis034
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Clinical Outcome of Severe Falciparum Malaria in African Children: Findings From a Large Randomized Trial

Abstract: Four predictors were independently associated with an increased risk of death: acidosis, cerebral manifestations of malaria, elevated blood urea nitrogen, or signs of chronic illness. The standard base deficit was found to be the single most relevant predictor of death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
187
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(203 citation statements)
references
References 72 publications
(74 reference statements)
13
187
2
1
Order By: Relevance
“…Earlier studies have shown that these two factors were good prognostic indicators of poor outcome in severe malaria 3,25,26 . The association between hypoglycaemia and death in this study is however at variance with the report by von Seidlein et al, 13 in which no association was found. Hypoglycaemia is reversible if detected early, but many of the patients in this study might have presented late such that irreversible tissue damage had occurred.…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…Earlier studies have shown that these two factors were good prognostic indicators of poor outcome in severe malaria 3,25,26 . The association between hypoglycaemia and death in this study is however at variance with the report by von Seidlein et al, 13 in which no association was found. Hypoglycaemia is reversible if detected early, but many of the patients in this study might have presented late such that irreversible tissue damage had occurred.…”
Section: Discussioncontrasting
confidence: 87%
“…A recent study with a large number of African children, in which predictors of deaths due to severe malaria were evaluated, did not report findings on oxygen saturation 13 . The current report is probably the first to prospectively evaluate the effects of hypoxaemia on outcome of admission among children with severe falciparum malaria in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In areas where malaria is endemic, approximately 70% of deaths occur in children age under 5 due to the lack of protective semi-immune status which is likely to be acquired after repeated bouts of infections [34]. Base deficit, impaired consciousness, convulsions, elevated blood urea, and underlying chronic illness were identified as the key prognostic indicators in children [35]. In non-endemic area, population generally lacks protective immunity and case fatality rate is almost 6 times greater among elderly patients [36].…”
Section: Factors Influencing Clinical Outcomesmentioning
confidence: 99%
“…It will be very interesting if this hypothesis is correct; however, technical issues relating to the use of primary, nonbrain cells and immortalized brain endothelial cells provide an alternative explanation for these results. The inconsistent association between overall parasitemia and CM observed in patients (12) prompts the question of whether the rupture of infected erythrocytes alone entirely explains the loss of brain endothelial barrier integrity in CM. A simple answer for the observed tissue-specific response in CM is that edema in the brain, unlike in other organs, can be particularly detrimental because of the confines of the skull and thus brain endothelial cells have specific responses to stimuli.…”
Section: At1 and At2 As Potential Therapeutic Targetsmentioning
confidence: 99%